Enhancing Patient-Centered Care Through Process Improvement: A Systematic Review of patient Satisfaction Outcomes - ALObaid, Saleh Khalil; Alzahrani, Ahmed Mohsen Mohamed; Alsharif , Fayez Salem; Alomar, Abdulkhaleq Essa Hassan; Almustanyir, Hadi Masoud Saleh; Sagr, Abdulaziz Ali; Alsomali, Saeed Ali Yousef; Alkhatib, Mohamad Ibrahim; Turkistani, Nawaf Anwar; Alawi, Ali Ahmed (Journal of Ecohumanism, 2024)
Patient-centered care has become a cornerstone in modern healthcare, focusing on personalized, respectful, and effective treatment that meets patients' unique needs and preferences. Process improvement methodologies, such as Lean, Six Sigma, and workflow optimization, have been increasingly adopted to streamline healthcare operations, reduce inefficiencies, and improve the quality of care. However, the specific impact of these methodologies on patient satisfaction within patient-centered care frameworks remains to be systematically evaluated. This systematic review aims to examine the effects of Lean, Six Sigma, and workflow optimization on patient satisfaction outcomes in patient-centered care settings, offering evidence-based insights for healthcare providers and policymakers.A comprehensive search was conducted across multiple databases, including PubMed, CINAHL, and Cochrane Library, to identify studies published from 2016 onward that evaluated patient satisfaction outcomes related to Lean, Six Sigma, and workflow optimization within patient-centered care models. Eligible studies were screened, assessed for quality, and analyzed based on patient satisfaction outcomes. Data extraction and quality assessments followed PRISMA guidelines.Findings from the selected studies indicate that process improvement methodologies positively impact patient satisfaction, with notable improvements in wait times, care coordination, and communication quality. Lean and workflow optimization showed a significant reduction in bottlenecks, while Six Sigma was associated with error reduction and standardized practices, contributing to higher patient satisfaction scores.Lean, Six Sigma, and workflow optimization methodologies offer promising avenues to enhance patient-centered care by improving patient satisfaction metrics. These methodologies provide healthcare organizations with structured approaches to meet patient needs more effectively and consistently, reinforcing the critical role of process improvement in achieving high-quality, patient-centered healthcare.